Macroalgal detritus and food-web subsidies along an Arctic fjord depth-gradient - Renaud, Paul E.; Løkken, Therese S.; Jørgensen, Lis L.; Berge, Jørgen; Johnson, Beverly J. (Frontiers in Marine Science, 2015)
Tight coupling between pelagic and benthic communities is accepted as a general principle on Arctic shelves. Whereas this paradigm has been useful for guiding ecological research, it has perhaps led to a disproportionate focus on POM and ice algae as the most likely sources of carbon for the benthic food web. Arctic shelves are complex systems, including banks, fjords, and trough systems up to 350 m or more in depth. In this stable-isotope study, thirteen different potential carbon sources were analysed for their contribution to the food-webs of Isfjorden, Svalbard. A mixing model with herbivorous copepods and grazing sea urchins as end-members was applied to determine the relative contributions of the most likely carbon sources to pelagic and benthic taxa. Most taxa from the benthos feed on a broad mixture of POM and macroalgal detritus, even at depths down to 410 m. Most suspension-feeding bivalves had isotopic signals consistent with more than a 50% contribution from kelps and rockweeds. In contrast, nearly all pelagic species had diets consistent with an overwhelming contribution of pelagic POM. These results indicate that macroalgal detritus can contribute significantly to near-shore Arctic food-webs, a trophic link that may increase if macroalgae increase in the Arctic as predicted. These weaker quantitative links between pelagic and benthic components of coastal systems highlight the need for thorough sampling of potential carbon-baselines in food-web studies. A large detrital-carbon component in diets of Arctic benthos may dampen the impacts of strong seasonality in polar primary producers, leading to higher ecosystem resilience, but may also result in lower secondary productivity.